Kebutuhan E-Modul Interaktif Basidiomycota berbasis Case Study dengan Mengintegrasikan QR Code: The Need for a Basidiomycota Case Study-based Interactive E-Module by Integrating QR Codes - Harlis, Harlis; Aswan, Dara Mutiara; Wulandari, Indi Rizki (BIODIK, 2024)
Mycology is one of the courses in the Biology Education Study Program, FKIP, Jambi University. Based on the results of the needs analysis, one of the materials that was considered quite difficult was the Basidiomycota material. This difficulty is because the Basidiomycota material has many species, there are many terms, and there is a lack of teaching materials. Based on the results of the analysis, appropriate learning methods are needed and to maximize them, they are assisted by teaching materials. This research aims to determine the needs of lecturers and students for Case Study-based Basidiomycota Interactive E-Modules by Integrating QR Codes. This research is a qualitative descriptive study carried out at the Faculty of Teacher Training and Education, Jambi University from May to June 2023. The subjects of this research are lecturers who teach mycology courses and students of the Jambi University FKIP Biology Education Study Program who contract the Mycology course. Data was collected through distributing questionnaires in the form of Google forms and interviews. The results of the analysis of the needs of lecturers teaching mycology courses show that mycology learning is generally carried out using discussion methods assisted by media in the form of powerpoint (PPT). The results of the analysis of student needs indicate that Basidiomycota material is one of the materials that is difficult to study in mycology courses. It was concluded that lecturers and students need a Case Study-based Basidiomycota Interactive E-Module by integrating QR Code.Key words: Learning media, Learning methods, Mushrooms, Teaching materialsAbstrakMikologi merupakan salah satu mata kuliah di Program Studi Pendidikan Biologi FKIP Universitas Jambi. Berdasarkan hasil analisis kebutuhan, salah satu materi yang dianggap cukup sulit yaitu materi Basidiomycota. Kesulitan tersebut dikarenakan materi Basidiomycota memiliki banyak spesies, terdapat banyak istilah, dan kurangnya bahan ajar. Berdasarkan hasil analisis dibutuhkan metode pembelajaran yang sesuai dan untuk memaksimalkannya dibantu dengan bahan ajar. Penelitian ini bertujuan untuk mengetahui kebutuhan dosen dan mahasiswa terhadap E-Modul Interaktif Basidiomycota berbasis Case Study dengan Mengintegrasikan QR Code. Penelitian ini merupakan penelitian deskriptif kualitatif yang dilaksanakan di Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi pada bulan Mei hingga Juni 2023. Subjek penelitian ini adalah dosen pengampu mata kuliah mikologi dan mahasiswa Program Studi Pendidikan Biologi FKIP Universitas Jambi yang mengontrak mata kuliah Mikologi. Data dikumpulkan melalui penyebaran angket berupa google form dan wawancara. Hasil analisis kebutuhan dosen pengampu mata kuliah mikologi diketahui bahwa pembelajaran mikologi umumnya dilaksanakan dengan menggunakan metode diskusi yang dibantu dengan media berupa powerpoint (PPT). Hasil analisis kebutuhan mahasiswa menyebutkan bahwa materi Basidiomycota merupakan salah satu materi yang sulit dipelajari pada mata kuliah mikologi. Disimpulkan bahwa dosen dan mahasiswa membutuhkan E-Modul Interaktif Basidiomycota berbasis Case Study dengan Mengintegrasikan QR Code.Kata kunci: Bahan ajar, Jamur, Media pembelajaran, Metode pembelajaran